Impact of Credit Amount and Nonperforming Loan on Financial Perfor-mance in Institution Moris Rasik Finance Service S.A By Mediating Interest Rates in the Branch Office Oe-Cusse - Timo, Fredio Lopes; Belo, Teresa Freitas; Amaral Menezes, Alvaro do (Al Makki Publisher, 2025)
This study aims to evaluate the impact of credit amount and non-performing loans (NPLs) on the financial performance of Moris Rasik Finance Service S.A. in Timor-Leste, with interest rates acting as a mediator. A survey research design was used, with a sample of 275 clients selected through purposive sampling. Data was collected via questionnaires and analyzed using Structural Equation Modeling (SEM) with Smart PLS 4.0. The results indicate that credit amount and NPLs have a significant impact on financial performance, while interest rates do not significantly affect financial performance. In conclusion, effective credit and NPL management can improve financial performance, whereas interest rates do not play a significant role. This study recommends strengthening credit monitoring and NPL risk management systems to enhance the overall financial performance of the institution.